High-order finite-volume methods for compressible multiphase flows using unstructured meshes - Adebayo, Ebenezer Mayowa (Cranfield University, 2023)
For the simulation of multi-component or multiphase compressible flows, presented in this thesis is a computationally efficient high-resolution numerical methods that capture shocks and interfaces in the finite-volume framework on unstructured grids. The robustness of the CWENO high-order schemes in capturing and resolving the material interface in multi-component or multiphase flows in the presence of strong gradients and material discontinuities with oscillation-free solutions and reduced numerical diffusion is demon- strated using the diffuse interface framework implemented in the open-source unstru- ctured compressible flow UCNS3D. The UCNS3D is an in-house code in the finite volume framework written in FORTRAN that is being actively developed by members of Cranfield University. For this research, some additional multiphase features were implemented in the code and continuously improved throughout this thesis. Stringent two- and three-dimensional compressible multiphase/multi-component test cases, including cavitation, were employed to assess the numerical methods. Results were compared with other high-order methods and existing experiments, demonstrating that CWENO is less dissipative, eliminates spurious oscillations at material boundaries, and provides a high-resolution description of material interfaces with minimal artificial smearing. These findings highlight CWENO’s superior capability in accurately simulating complex multiphase or multi-component phenomena in compressible flows.
Keywords: oscillation free; numerical diffusion; compressible flow; FORTRAN; two-dimensional; three-dimensional